Effect of Cloxacillin on Bilirubin-albumin Binding - Achmad Surjono (Indonesian Pediatric Society, 1993)
Cloxacillin is usually given to newborn infants with sepsis in particular for penicillinase-producing staphylococcus aureus. The effect of cloxacillin on bilirubin-albumin binding was investigated in vitro using the peroxidase oxidation method with human albumin (bilirubin 0.255 mM, albumin 0.45 mM, billalb 0.56, pH 7.4, temperature 3 0Â°C). Sulfisoxazole, a drug which is capable of displacing bilirubin from albumin was used as control. The displacement constant of cloxacillin was 4.86 x 1o5 Nr1, stronger than that of sulfisoxazole (1. 72 x 104 M-1). Both drugs were capable of displacing bilirubin as determined by their maximal displacement factors of 2.21 and 2.29, respectively. Since cloxacillin apparently increases the risk of bilirubin encephalopathy the use of this drug in jaundiced newborns with sepsis, especially in the premature infants, should be reconsidered.